Literacy learning in the early years - Rohl, Mary; Barratt-Pugh, Caroline (Allen & Unwin, 2000)
This introduction to early literacy learning covers the much neglected field of literacy needs of children aged 0-5, as well as the early school years up to age 8. The authors take a socio-cultural approach to literacy learning, emphasising the importance of understanding the contexts of literacy practices.